Small signal modeling of restructured boost converter in continuous conduction mode - Muqorobin, Anwar; Wijanarko, Sulistyo; Kasim, Muhammad; Irasari, Pudji; Wirtayasa, Ketut; Widiyanto, Puji (Institute of Advanced Engineering and Science, 2025)
This paper introduces small signal modeling of the restructured boost converter (RBC) in continuous conduction mode (CCM) by using the circuit averaging technique. The averaging technique produces linear transfer functions of the converter. The transfer functions relating the duty cycle to output voltage, duty cycle to inductor current, input voltage to output voltage, and input voltage to inductor current are obtained. To validate the converter model, power simulation (PSIM) simulations are developed, and experiments are conducted. The function of RBC is similar to a conventional boost converter, i.e., to level up the input voltage. A comparative analysis between the RBC and conventional boost converter is performed. The results highlight the advantages of RBC over a conventional boost converter.